Inteligentna organizacja jako źródło sukcesu organizacji na wybranym przykładzie: Intelligent organization as a source of success - case studies - Ginter, Agnieszka; Kałuża, Halina (Management and Administration Journal, 2021)
Conception of an intelligent organization was introduced to the theory and practice ofmanagement as the answer to the transformation process of the contemporary economy. Thisis undoubtedly a challenge for organizations which are located in the Mazovia area. Now, thetraditional structure and the management model there, are less useful for the new forms, as theresults of 26 firms in the year 2012 allow to estimate their intelligence. The intelligent organization’s features, which were diagnosed, permit us to say, that the researched companies are atthe initial stage of knowledge management, as it should take place in intelligent organizations.